2021
DOI: 10.3844/jcssp.2021.251.264
|View full text |Cite
|
Sign up to set email alerts
|

Financial Forecasting with Machine Learning: Price Vs Return

Abstract: Forecasting directional movement of stock price using machine learning tools has attracted a considerable amount of research. Two of the most common input features in a directional forecasting model are stock price and return. The choice between the former and the latter variables is often subjective. In this study, we compare the effectiveness of stock price and return as input features in directional forecasting models. We perform an extensive comparison of the two input features using 10-year historical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…This is in line with studies like Naser (2016) and Drachal (2016) who used WTI crude oil as a proxy of crude oil. In line with Firuz, Gurrib and Rajab (2021) who find that prices to be a more effective input feature than return for US large stocks, we source daily price data, from 9 November 2018 to 23 December from Factset and Borsa Italiana. Public holidays in Italy are excluded.…”
Section: Datamentioning
confidence: 99%
“…This is in line with studies like Naser (2016) and Drachal (2016) who used WTI crude oil as a proxy of crude oil. In line with Firuz, Gurrib and Rajab (2021) who find that prices to be a more effective input feature than return for US large stocks, we source daily price data, from 9 November 2018 to 23 December from Factset and Borsa Italiana. Public holidays in Italy are excluded.…”
Section: Datamentioning
confidence: 99%
“…Machine learning models have been used for forecasting in a variety of applications including finance [ 9 , 10 ], energy [ 11 ], education [ 12 ], temperature [ 13 ], and many others. A number of authors have employed ML methods such as regularized linear regression (LASSO) and recurrent neural networks (RNN) to forecast the spread of the infection [ 14 ].…”
Section: Literaturementioning
confidence: 99%
“…For instance, Smith et al ( 2016 ) reported that 20% of hedge funds used technical analysis. Kamalov et al ( 2021 ) forecasted the direction of U.S. large-cap stocks and found that adding technical indicators equalized the effectiveness of return and price as inputs in machine learning models. Gencay ( 1999 ) found gains in foreign currency markets, with Olson ( 2004 ) further supporting that risk-adjusted trading rule gains gradually fell as time passed.…”
Section: Literature Reviewmentioning
confidence: 99%